Exploring the Effectiveness of Hydrophobic Glass Surface on Touch-Enabled Digital Device to Reduce Microbial Adhesion and Propagation - Premkumar Sowmya Vithya; Manimuthu Mani Sankar (Wolters Kluwer Medknow Publications, 2024)
This study investigates the effectiveness of hydrophobic glass surfaces in reducing microbial populations on touch-enabled digital devices. Hydrophobic coatings have been proposed as a potential solution to minimize microbial adhesion and growth on device surfaces. Here, we intended to investigate the effect of hydrophobic spray on microbial load. The results were quantitatively analyzed using microbiological techniques. the nonhydrophobic surface harbors gradual microbial buildup upon time, such as threefold increase from 2 to 4 h and fivefold increase to 6 h post initial sampling with 143.6 ± 33.89 cfu/ml increase up to 264.7 ± 28.53 cfu/ml, whereas the hydrophobic surface had an overall build-up from 16.6 ± 1.2 to 50.45 ± 11.12 cfu/ml with P < 0.0001 significance. This research provides valuable insights into the potential application of hydrophobic glass coatings to mitigate microbial contamination on touch-enabled digital devices, enhancing their hygienic properties and minimizing the risk of infectious disease transmission.